Shapes of subcortical structures in adolescents with and without familial history of substance use disorder. Issue 9 (7th April 2022) - Wang, Zhishun; Rodriguez‐Moreno, Diana V.; Cycowicz, Yael M.; Amsel, Lawrence V.; Cheslack‐Postava, Keely; He, Xiaofu; Ryan, Megan; Geronazzo‐Alman, Lupo; Musa, George J.; Bisaga, Adam; Hoven, Christina W.
Abstract: It has been suggested that intergenerational transmission of risk for substance use disorder (SUD) manifests in the brain anatomy of substance naïve adolescents. While volume and shapes of subcortical structures (SSS) have been shown to be heritable, these structures, especially the pallidum, putamen, nucleus accumbens, and hippocampus, have also been associated with substance use disorders. However, it is not clear if those anatomical differences precede substance use or are the result of that use. Therefore, we examined if volume and SSS of adolescents with a family history (FH+) of SUD differed from adolescents without such a history (FH−). Because risk for SUD is associated with anxiety and impulsivity, we also examined correlations between these psychological characteristics and volume/SSS. Using structural MRI and FSL software, we segmented subcortical structures and obtained indices of SSS and volumes of 64 FH+ and 58 FH− adolescents. We examined group differences in volume and SSS, and the correlations between volume/SSS and trait anxiety and impulsivity. FH+ adolescents had a significant inward deformation in the shape of the right anterior hippocampus compared to FH− adolescents, while the volume of this structure did not differ between groups. Neither shape nor volume of the other subcortical structures differed between groups. In the FH+ adolescents, the left hippocampus shape was positively correlated with both trait anxiety and impulsivity, while in FH− adolescents a negative correlation pattern of SSS was seen in the hippocampus. SSS appears to capture local anatomical features that traditional volumetric analysis does not. The inward shape deformation in the right anterior hippocampus in FH+ adolescents may be related to the known increased risk for behavioral dysregulation leading to SUD in FH+ offspring. Hippocampus shape also exhibits opposite patterns of correlation with anxiety and impulsivity scores across the FH+ and FH− adolescents. These novel findings may reveal neural correlates, not captured by traditional volumetric analysis, of familial transmission of increased vulnerability to SUD. Abstract : Shapes of subcortical structures capture local anatomical features that traditional volumetric analysis does not. The inward shape deformation in the right anterior hippocampus in the adolescents with a positive family history (FH+) of substance use disorder (SUD) may be related to the known increased risk for behavioral dysregulation leading to SUD in FH+ offspring.